Retracted: Genotyping pattern of hepatitis C virus among patients on maintenance haemodialysis at tertiary care hospitals of Pune, Maharashtra, India - Patel, Anubha; Murthy, Ramanesh; Baghel, Ashish; Roy, Partha; S. Lole, Kavita (International Journal of Research in Medical Sciences, 2018)
The article titled, "Genotyping pattern of hepatitis C virus among patients on maintenance haemodialysis at tertiary care hospitals of Pune, Maharashtra, India", published in the International Journal of Research in Medical Sciences, Volume 6, Issue 4, 2018, Pages 1435-1439, DOI: http://dx.doi.org/10.18203/2320-6012.ijrms20181310 is being retracted. We received complaint from one of the co-authors, after publication of the article that corresponding author, Dr. Anubha Patel had submitted the manuscript without informing other co-authors and analysis was not comprehensive. We contacted the corresponding author who could not satisfactorily respond to our queries. Since the author could not satisfactorily defend her paper and contravened the declaration she made while submitting her manuscript, it was decided to retract the article from International Journal of Research in Medical Sciences and not to consider any manuscript submitted by her in future.